THE INFLUENCE OF SOCIAL MEDIA CONTENT AND MENTAL HEALTH CONDITION ON PURCHASE INTENTION AT SHOPEE (CASE STUDY: STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY OF NORTH SUMATRA) - Clarisa Felicia; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Universitas Efarina, 2023)
This research aims to know the influence of Social Media Content and Mental Health Conditions on Purchase Intention. The population and sample in this study were 30 mahasiswa aktif yang aktif di media sosial dan bersedia berpartisipasi terhadap penelitian ini with the sampling technique being accidental sampling. The data analysis technique used is multiple linear regression statistical analysis. The primary data used in this study consisted of social media content and mental health conditions on purchase intention. The results of this research show that Based on the partial test (t test), the Social Media Content and Mental Health Condition have a significant effect on the variables of the Purchase Intention, the simultaneous test (f-test), Social Media, and Mental Health Condition have a significant effect on the variables of the Purchase Intention.